(untitled) (Journal of Pharma Insights and Research, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by the profound loss of dopaminergic neurons in the substantia nigra pars compacta and the intracellular aggregation of alpha-synuclein, forming Lewy bodies. This neuropathological process manifests clinically through cardinal motor symptoms—bradykinesia, resting tremor, rigidity, and postural instability—complemented by a complex array of non-motor symptoms, including autonomic dysfunction, cognitive impairment, and sleep disorders, which significantly impair quality of life. The etiology of PD is multifactorial, involving a complex interplay of genetic predispositions, such as mutations in LRRK2 or SNCA, and environmental risk factors, including pesticide exposure. Diagnosis remains primarily clinical, guided by established criteria, though advanced imaging like dopamine transporter scanning offers valuable support. Management is symptomatic, with levodopa therapy representing the gold standard for motor symptom control. However, long-term levodopa use is associated with motor complications, necessitating sophisticated management strategies. A holistic, multidisciplinary approach combining pharmacological treatment, physiotherapy, and patient support is essential. Current research is invariably focused on identifying disease-modifying therapies that can stop or reverse the underlying neurodegenerative cascade, representing the foremost therapeutic goal